Analysis of Phenolic Compounds in Wood Vinegar and Smoke from Burning Coconut Shell by Head Space Solid Phase Micro Extraction-Gas Chromatography-Mass Spectrometry - กฤษณะพุกต์ ธัญวรรณ; ลิ่มทองวิรัตน์ วัฒนาพร; โตกะหุต สาวิตรี; ไชยสิทธิ์ สุวรรณ (KKU Science Journal, 2014)
The investigation of this project was to study the performance of 2 differences SPME fibers that is 75 µm Carboxen/PDMS and 65 µm PDMS/DVB. In this analysis, phenol compounds in wood vinegar were found and compared with smoke from burning coconut shell by Head Space Solid Phase Micro Extraction-Gas Chromatography-Mass Spectrometry. It was found that in wood vinegar using Carboxen/PDMS fiber we found 10 types of phenol compounds and using PDMS/DVB fiber we found 14 types of phenol compounds. In smoke from burning coconut shell we found 17 types of phenol compounds equally. Phenol is the most abundant phenolic compounds in both wood vinegar and smoke from burning coconut shell. PDMS/DVB is more effective for the extraction of phenolic compounds than Carboxen/PDMS.